1986
DOI: 10.1111/j.1469-8137.1986.tb00587.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF WINTER FIELD CONDITIONS ON THE DISTRIBUTION OF TWO SPECIES OF UMBILICARIA

Abstract: SUMMARYUmbilicaria vellea (L.) Ach. and U. deusta (L.) Baum. have distribution patterns that are mutually exclusive. U. vellea occurs in vertically inclined microsites that are permanently snow-free. In contrast, U. deusta occurs on flat or gently sloping surfaces that receive a substantial snow cover. Earlier field work had suggested that this distribution pattern was maintained, at least in part, by the inability of U. vellea to store photosynthetic products and thereby maintain a positive carbon balance whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Acta 109(1996) 292 -298 © Georg Thieme Verlag Stuttgart· New York Lichens are able to withstand long-term continuous freezing and alternating periods of freezing and thawing (e.g. Scott and Larson, 1986). Lichens also have the capacity of photosynthesizing and respiring at temperatures below DOC (see Kappen et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Acta 109(1996) 292 -298 © Georg Thieme Verlag Stuttgart· New York Lichens are able to withstand long-term continuous freezing and alternating periods of freezing and thawing (e.g. Scott and Larson, 1986). Lichens also have the capacity of photosynthesizing and respiring at temperatures below DOC (see Kappen et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that many lichen species have an extremely high freezing tolerance when air-dry, being unaffected after exposure to temperatures as low as )196°C (Kappen & Lange 1972;Larson 1978). However, when hydrated, lichens are more susceptible to freezing, which is probably due to ice formation within cells (Kappen & Lange 1972;Larson 1982;Scott & Larson 1986;Nash et al 1987;Benedict 1990). Nevertheless, like plants, lichens do have mechanisms to avoid intracellular ice crystallisation; extracellular ice nucleation removes most liquid water before damaging intracellular ice formation processes are initiated (Burke et al 1976;Ashworth & Kieft 1992;Schroeter & Scheideg-Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that many lichen species have an extremely high freezing tolerance when air‐dry, being unaffected after exposure to temperatures as low as −196 °C (Kappen & Lange 1972; Larson 1978). However, when hydrated, lichens are more susceptible to freezing, which is probably due to ice formation within cells (Kappen & Lange 1972; Larson 1982; Scott & Larson 1986; Nash et al. 1987; Benedict 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations